1982
DOI: 10.1111/j.1524-4725.1982.tb02679.x
|View full text |Cite
|
Sign up to set email alerts
|

“Small” Melanomas. Relation of Prognostic Variables to Diameter of Primary Superficial Spreading Melanomas

Abstract: In a consecutive series of 648 superficial spreading melanomas a significantly better 5-year disease-free survival rate was observed for patients whose primary tumors were 14 mm or less in diameter when compared with those 15 mm or larger in diameter. Other distinguishing features of the group of "smaller" superficial spreading melanomas were that they occurred in younger patients; were of shorter durations; were more common in women; occurred disproportionately on the lower limbs; were less elevated; tended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…66 In general, small-diameter tumors are more likely to be thinner or in situ when compared with larger diameter melanomas. [67][68][69] Total body photography has been advocated by many authors to document stability or instability of nevi in people at high risk for cutaneous melanoma. 66 The philosophy behind the use of total body photography is that relatively subtle changes in preexisting nevi that might otherwise be overlooked without baseline photography might be detected at an earlier time.…”
Section: Photographymentioning
confidence: 99%
“…66 In general, small-diameter tumors are more likely to be thinner or in situ when compared with larger diameter melanomas. [67][68][69] Total body photography has been advocated by many authors to document stability or instability of nevi in people at high risk for cutaneous melanoma. 66 The philosophy behind the use of total body photography is that relatively subtle changes in preexisting nevi that might otherwise be overlooked without baseline photography might be detected at an earlier time.…”
Section: Photographymentioning
confidence: 99%
“…Selected Literature : We have previously reported that MM with diameters of 14 mm or less have a significantly better prognosis than those that are of larger diameter (Kopf et al, 1982). However, a smaller diameter alone does not assure survival.…”
Section: Section IIImentioning
confidence: 99%
“…42 High-risk patients with periodic surveillance tend to have significantly thinner, less invasive melanomas and small-diameter lesions compared with those whose tumors are self-diagnosed. [43][44][45][46][47] Changes in small-diameter tumors might be overlooked in the absence of archival images. The surveillance interval commonly accepted by dermatologists is annually or every 4 to 6 months.…”
Section: Commentmentioning
confidence: 99%